2020
DOI: 10.1016/s2213-2600(20)30134-x
|View full text |Cite
|
Sign up to set email alerts
|

Rational use of face masks in the COVID-19 pandemic

Abstract: Since the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that caused coronavirus disease 2019 (COVID-19), the use of face masks has become ubiquitous in China and other Asian countries such as South Korea and Japan. Some provinces and municipalities in China have enforced compulsory face mask policies in public areas; however, China's national guideline has adopted a risk-based approach in offering recommendations for using face masks among health-care workers and the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
1,196
1
58

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,271 publications
(1,270 citation statements)
references
References 0 publications
15
1,196
1
58
Order By: Relevance
“…Perhaps, this led to significantly higher face-mask use by second-survey respondents, regardless of the presence of symptoms. This is an interesting and important phenomenon due to the divided scientific opinion on protective effects of usual face masks 19,28 , coupled with their scarce availability. Efforts are needed to impart an unbiased and clear guidelines on the use of face masks and their types to allay the fears, confusions and sense of inferiority (for people with no access to the masks) among general population.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, this led to significantly higher face-mask use by second-survey respondents, regardless of the presence of symptoms. This is an interesting and important phenomenon due to the divided scientific opinion on protective effects of usual face masks 19,28 , coupled with their scarce availability. Efforts are needed to impart an unbiased and clear guidelines on the use of face masks and their types to allay the fears, confusions and sense of inferiority (for people with no access to the masks) among general population.…”
Section: Discussionmentioning
confidence: 99%
“…Individual behaviour is crucial in controlling the spread of COVID-19. In early March 2020 Anderson et al (2020) described that in Western democracies personal action, rather than government action, might be the most important issue comprising of early self-isolation (within one day from symptom onset), seeking medical advice remotely unless symptoms are severe, and physical distancing. The same authors described the importance of the application of a combination of mitigation measures such as physical distancing in combination with the ban of mass gatherings, good diagnostic facilities and remotely accessed health advice, together with specialised treatment for people with severe COVID-19 infections.…”
Section: Socio-economic Restrictionsmentioning
confidence: 99%
“…Niu et al (2020) reported that transmission by people with mild or no symptoms can undermine the effectiveness of the isolation strategy because of reduced likelihood of isolating all cases and tracing all contacts. The identification and testing of potential cases needs therefore to be as extensive as is permitted by healthcare and diagnostic testing capacity-including the identification, testing, and isolation of suspected cases with no or mild disease (e.g., influenza-like illness).…”
Section: Socio-economic Restrictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…
The current COVID-19 pandemic has led to a dramatic shortage of masks and other personal protective equipment (PPE) in hospitals around the globe [1]. One component of PPE that is in particular demand are disposable N95 face masks.
…”
mentioning
confidence: 99%